Tat-Endophilin A1 Fusion Protein Protects Neurons from Ischemic Damage in the Gerbil Hippocampus: A Possible Mechanism of Lipid Peroxidation and Neuroinflammation Mitigation as Well as Synaptic Plasticity - Jung, Hyo Young (Cells, 2021)
The present study explored the effects of endophilin A1 (SH3GL2) against oxidative damage brought about by H(2)O(2) in HT22 cells and ischemic damage induced upon transient forebrain ischemia in gerbils. Tat-SH3GL2 and its control protein (Control-SH3GL2) were synthesized to deliver it to the cells by penetrating the cell membrane and blood–brain barrier. Tat-SH3GL2, but not Control-SH3GL2, could be delivered into HT22 cells in a concentration- and time-dependent manner and the hippocampus 8 h after treatment in gerbils. Tat-SH3GL2 was stably present in HT22 cells and degraded with time, by 36 h post treatment. Pre-incubation with Tat-SH3GL2, but not Control-SH3GL2, significantly ameliorated H(2)O(2)-induced cell death, DNA fragmentation, and reactive oxygen species formation. SH3GL2 immunoreactivity was decreased in the gerbil hippocampal CA1 region with time after ischemia, but it was maintained in the other regions after ischemia. Tat-SH3GL2 treatment in gerbils appreciably improved ischemia-induced hyperactivity 1 day after ischemia and the percentage of NeuN-immunoreactive surviving cells increased 4 days after ischemia. In addition, Tat-SH3GL2 treatment in gerbils alleviated the increase in lipid peroxidation as assessed by the levels of malondialdehyde and 8-iso-prostaglandin F2α and in pro-inflammatory cytokines such as tumor necrosis factor-α, interleukin-1β, and interleukin-6; while the reduction of protein levels in markers for synaptic plasticity, such as postsynaptic density 95, synaptophysin, and synaptosome associated protein 25 after transient forebrain ischemia was also observed. These results suggest that Tat-SH3GL2 protects neurons from oxidative and ischemic damage by reducing lipid peroxidation and inflammation and improving synaptic plasticity after ischemia.